The Use of Continuous Glucose Monitoring Systems in the Diagnosis and Monitoring of Gestational Diabetes Mellitus and Diabetes in Pregnancy - A Review of the Literature - Kacper Lenart; Julia Kwaśna; Adrianna Załęska; Szymon Bednarek; Izabela Kaźmierczyk; Mateusz Górski; Michał Homza; Mateusz Bychowski; Natalia Zakrzewska; Joanna Kulicka (Quality in Sport)
Background: Gestational diabetes mellitus (GDM) and preexisting diabetes present significant risks to maternal and neonatal health. Continuous glucose monitoring (CGM) has emerged as a valuable tool for optimizing glycemic control during pregnancy, offering real-time data and insights beyond traditional methods.